(untitled) (Academia Journal of Medicine, 2021)
Background: To assess effectiveness of Dapagliflozin as add-on therapy for the treatment of Type 2 Diabetes Mellitus. Method: Dapaglifozin was added as add on treatment in all the patients after the initial standard management. They were divided into groups based on the initial combinations with comparable baseline readings for HbA1c and fasting blood glucose (FBG). Differences in the values of HbA1c and FBG following treatment with Dapagliflozin was evaluated at 3 months. Result: Among all 130 subjects, the 56.92% were males and 43.08% were females. Maximum subjects belonged to the age group of 50-59 years. The mean age of the subjects was 54.02 years. Out of 130 subjects, 29.23% had a history of T2DM. Most of the subjects had T2DM from last 8-10 years (53.08%), Out of 130 subjects, 16.92% had hypertension, 10.77% had cardiovascular disease and 6.15% had other co-morbidities. The mean body weight and height among the subjects after the intervention was 68.96Kg and 162.09 respectively. Glycemic parameters among the study subjects after the intervention showed a mean HbA1c value of 7.05%, mean FBG value of 131.73mg/dl and mean PPBG value of 204.98mg/dl. Mean HbA1c level achieved after 6 months of Dapagliflozin treatment was 7.62% in our patient population. Conclusion: Dapagliflozin was well tolerated in patients with T2DM and it lowered HbA1c levels and body weight after the intervention compared to baseline. The study found no adverse effect, implying that Dapaglifozin has a tolerable tolerability profile.